Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/0256-307x/35/9/090303
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Interference Constructed by Two Hong–Ou–Mandel Effects in One Mach-Zehnder Interferometer

Abstract: We present a two-photon interference experiment in a modified Mach-Zehnder (MZ) interferometer in which two Hong-Ou-Mandel effects occur in tandem and construct superposed two-photon states. The signal photons pass both the arms of the MZ interferometer while the idler photons pass one arm only. Interestingly, the probability of the idler photons emerging from any output port still shows a sine oscillation with the two-photon phase difference and it can be characterized only by the indistinguishability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…[1] In the same year, Ou et al reported a similar interference experiment with blue and green laser light beams. [2] The second-order interference of photons with different spectra were further studied with photons generated by spontaneous parametric down-conversion, [3][4][5][6][7][8][9][10][11] spontaneous Raman process, [12] single-photon sources, [13] laser and singlephoton source, [14] and chirped laser pulses, [15] etc. The above experiments can be categorized into two groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In the same year, Ou et al reported a similar interference experiment with blue and green laser light beams. [2] The second-order interference of photons with different spectra were further studied with photons generated by spontaneous parametric down-conversion, [3][4][5][6][7][8][9][10][11] spontaneous Raman process, [12] single-photon sources, [13] laser and singlephoton source, [14] and chirped laser pulses, [15] etc. The above experiments can be categorized into two groups.…”
Section: Introductionmentioning
confidence: 99%
“…One group is that the two light beams of different spectra are incident to both input ports of a Shih-Alley/Hong-Ou-Mandel (HOM) interferometer. [1][2][3][4][5][6][7][8][9][10][11][12]16,17] The other one is that two light beams are incident to two input ports of an HOM interferometer, respectively. [13][14][15] The first group of experiments [1][2][3][4][5][6][7][8]10,12] can be easily understood in quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%